Sildenafil citrate for the management of fetal growth restriction and oligohydramnios - Choudhary R (International Journal of Women's Health, 2016)
Rana Choudhary,1 Kavita Desai,2 Hetal Parekh,3 Kedar Ganla1 1Department of Reproductive Medicine, Ankoor Fertility Clinic, 2Department of Radiology, Dadar Imaging and Diagnostic Centre, 3IVF Department, Hiranandani Hospital, Mumbai, India Abstract: Fetal growth restriction (FGR) and preeclampsia are the major causes of neonatal morbidity and mortality, which affect up to 8% of all pregnancies. The pathogenesis in FGR is an abnormal trophoblastic invasion leading to compromised uteroplacental circulation. However, in spite of this understanding and identification of high-risk patients, the management options are limited. There are some new studies which have demonstrated the role of sildenafil citrate in improving vasodilatation of small myometrial vessels and therefore improvement in amniotic fluid index, fetal weight, and even uterine and umbilical artery Doppler patterns. We report here the case of a 31-year-old female with infertility and preconceptional thin endometrium responding well to sildenafil citrate, followed by conception. However, she presented with an early-onset FGR at 26 weeks of gestation, and again after treatment with sildenafil citrate, showed improvement in amniotic fluid index and fetal weight, finally resulting in delivery of a full-term healthy baby with uneventful neonatal course. Keywords: sildenafil citrate, fetal growth restriction, oligohydramnios, thin endometrium